THE MEANINGS OF SALUTATIONS AT ISLAMIC BOARDING SCHOOLS: AN ANTHROPOLOGICAL-LINGUISTIC STUDY (MAKNA SAPAAN DI PESANTREN: KAJIAN LINGUISTIK-ANTROPOLOGIS) - Millatuz Zakiyah (UIN Raden Mas Said Surakarta, 2018)
This research aims to explains the meaning of some specific address terms such as kiai, gus, ning, kang, etc. which are obligatorily used on pondok pesantren in Jombang. This study discusses the classification and the meanings of address terms in pesantren as well as pesantren and Javanese cultural perspectives on the terms. This descriptive-qualitative research applies emic approach. The result shows that there are 15 address terms in pesantren, namely kiai, nyai, gus, mas, ning, bapak, ibu, mbak, kang, cak, ustadz, ustadzah, abah, abi, and umi. These distinctive address terms aim to honor the kiai, teachers, kiai’s and teachers’families, and santri. Pesantren’s view posits that respecting teachers, teachers’ family, and fellow santri is a pace to get barokah and manfaat (benefit) of science, the santri’s ultimate goal and their destination of seeking knowledge. Meanwhile, Javanese cultural persepective argues that this respect indicates syncretism between Javanese and Islamic culture. The respect to kiai is influenced by the respect to begawan. On the other hand, santri’s attitude refers to cantrik. Different tributes between teacher and kiai are influenced by Javanese culture. It indicates the existence of different obligations and rights in pesantren which impact on the stratification at pesantren. The stratification at pesantren can bedivided into three classes; namely nursery class (kiai and his family), teacher class, and santri class.